2017
DOI: 10.1111/imm.12719
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome contributes to host protection during Sporothrix schenckii infection

Abstract: Sporotrichosis is a mycosis caused by fungi from the Sporothrix schenckii species complex, whose prototypical member is Sporothrix schenckii sensu stricto. Pattern recognition receptors (PRRs) recognize and respond to pathogen-associated molecular patterns (PAMPs) and shape the following adaptive immune response. A family of PRRs most frequently associated with fungal recognition is the nucleotide-binding oligomerization domain-like receptor (NLR). After PAMP recognition, NLR family pyrin domain-containing 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 74 publications
0
40
0
1
Order By: Relevance
“…A greater response of all these mediators was observed in the animals infected with the treated fungi, principally those that grew at the highest concentration of toluene (Fig 4). Several studies reveals that a Th1 and Th17 are stimulated during S. schenckii infection and they are important for the fungal clearance (Ferreira et al ., 2015; Gonçalves et al ., 2017; Batista-Duharte et al ., 2018). Interestingly, a recent report of our group reveled that both S. schenckii and the more virulent S. brasiliensis stimulate similar Th1 response, but S. brasiliensis induced a more severe disease associated with sustained Th17 and a regulatory T cells (Tregs) responses than S. schenckii (Batista-Duharte et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A greater response of all these mediators was observed in the animals infected with the treated fungi, principally those that grew at the highest concentration of toluene (Fig 4). Several studies reveals that a Th1 and Th17 are stimulated during S. schenckii infection and they are important for the fungal clearance (Ferreira et al ., 2015; Gonçalves et al ., 2017; Batista-Duharte et al ., 2018). Interestingly, a recent report of our group reveled that both S. schenckii and the more virulent S. brasiliensis stimulate similar Th1 response, but S. brasiliensis induced a more severe disease associated with sustained Th17 and a regulatory T cells (Tregs) responses than S. schenckii (Batista-Duharte et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Differences in immunogenicity between the different clinical isolates of S. schenckii sensu lato and the recognition of several fungal antigens by specific antibodies induced in infected human, cats and rodents have been reported (Fernandes et al, 2013;Della Terra et al, 2017). Moreover, some studies have addressed the role of the cellular-mediated immune response in sporotrichosis by evaluating the T helper immune response induced in vitro or in murine models of systemic S. schenckii sensu stricto infection (Uenotsuchi et al, 2006;Maia et al, 2006;Ferreira et al, 2015;Gonçalves et al, 2017). However, the role of Tregs in sporotrichosis has yet to be determined, and comparative studies of T cells response against different species of S. schenckii sensu lato have not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…A significant decrease in atherosclerotic lesion size has also observed at the aortic sinus of HFD-fed LDL-R⁻/⁻ mice reconstituted with NLRP3 knockout bone marrow cells [23]. In addition, previous studies have shown that NLRP3 recruits caspase-1, leading to the activation of caspase-1, maturation and secretion of IL-1β and IL-18, and initiation of pyroptosis [24][25][26][27]. Our results showed that the cardiac tissues in the HFD + TQ group expressed markedly reduced levels of NLRP3, caspase-1, IL-1β and IL-18 compared with that in the HFD group, indicating that TQ downregulated HFD-induced pyroptosis.…”
Section: Discussionmentioning
confidence: 89%